Protocol for a needle-trap device coupled to GC for the analysis of volatile and semi-volatile compounds in solid and liquid samples - Shakiba Zeinali; Janusz Pawliszyn (Green Analytical Chemistry, 2022)
With the growing demand for green analytical methods, reduced solvent consumption, and on-site sampling, the need for fast and accurate methods of detecting and quantifying organic compounds is becoming more and more apparent. Needle-trap devices (NTDs) are capable of satisfying many of these demands, as they combine sampling and preconcentration into a single device, while eliminating the need for solvents. After extraction, extracted compounds would be thermally desorbed and sent to GC instrument for separation and quantification. Furthermore, NTDs are small, which makes them a good candidate for on-site sampling. In establishing optimized sampling conditions, it is important to consider factors such as sampling volume, sorbent type and length, and temperature. The protocol presented in this paper is intended to provide a guideline for suitable NTD preparation. We begin by providing an overview of the fundamental and historical aspects of NTDs, followed by a discussion of some of the influential parameters involved in the proposed protocol. Next, a step-by-step protocol and troubleshooting guidelines are detailed, followed by an evaluation of the developed method. While NTDs can be used with different types of samples, the proposed protocol focuses on the application of NTDs for the extraction of volatile and semi-volatile compounds from solid and liquid samples including, but not limited to, environmental (water, soil, etc.) and biological (urine, blood, etc.) matrices.